2017
DOI: 10.1590/s0100-83582017350100051
|View full text |Cite
|
Sign up to set email alerts
|

Weed Community Interference and Phytosociological Studies in a Sweet Sorghum Crop

Abstract: -This research was carried out to evaluate the interference periods and phytosociological indexes of the weed community on sweet sorghum, hybrid CVSW 80007, cultivated for two seasons in a year. The treatments were based on an increased duration of weed presence and weed absence after sowing (0, 4, 7, 14, 21, 28, 35, 42, 56 and 68 days after crop emergence for the summer season and 0, 4, 7, 14, 21, 28, 35, 42, 49, 56, 63 and 100 days for the fall season). The weed community was evaluated based on the numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 10 publications
1
6
1
1
Order By: Relevance
“…In a study carried out under field conditions, the hybrid of sweet sorghum CVSW 80007 did not have its yield reduced by a weed community (mainly composed by C. rotundus and Alternanthera tenella Colla), even in a crop grown without any weed control (Giancotti et al, 2017). In the present study, that hybrid of sweet sorghum also showed high weed tolerance, even in a situation 7 of population disadvantage.…”
contrasting
confidence: 49%
See 1 more Smart Citation
“…In a study carried out under field conditions, the hybrid of sweet sorghum CVSW 80007 did not have its yield reduced by a weed community (mainly composed by C. rotundus and Alternanthera tenella Colla), even in a crop grown without any weed control (Giancotti et al, 2017). In the present study, that hybrid of sweet sorghum also showed high weed tolerance, even in a situation 7 of population disadvantage.…”
contrasting
confidence: 49%
“…as the weeds with a prevailing influence given their high infestation rate, fast grow, and capacity for shading. While many studies have investigated the growth and development of grain and forage sorghum in the presence of weeds, few have addressed interspecific competition between weeds and sweet sorghum (Giancotti et al, 2017). Given sweet sorghum's high natural resources use efficiency and robust growth of both above-and below-group portions of the plant, it can be expected that even in a physically limited environment and under high weed infestation rates, this type of sorghum would not suffer weed interference as severe as other types of sorghum.…”
Section: Introductionmentioning
confidence: 99%
“…The most important species were Digitaria ciliaris and Digitaria horizontalis, which made their infestation potential evident. The genus Digitaria has competitive weed species that are aggressive and difficult to manage, infesting many agricultural crops such as cowpea, sweet sorghum, cotton, banana and sugarcane (Oliveira & Freitas, 2008;Giancotti et al, 2017). They are perennial, erect grasses, which have striated stems and long internodes that ensures their dominance in the area.…”
Section: /9mentioning
confidence: 99%
“…The observations of Mishra et al [99] regarding the increased competitiveness of taller hybrids were similar. There is also evidence that S. bicolor cultivars have excellent allelopathic potential, since they were reported to have suppressed noxious weeds such as Cyperus rotundus (L.) and Ipomoea hederifolia L. [100]. Recent research has established that allelopathic genotype cultivars provide suppression to noxious weed species such as S. halepense, Echinochloa colona L. (Link), and Amaranthus retroflexus L.; weed suppression was attributed to the presence of phenolic acids on the root exudates of the crop plants [94].…”
Section: Weed Managementmentioning
confidence: 99%